Scan Angle Extension by Array with Pattern Reconfigurable Elements - Xiao, S.; Bai, Y.-Y.; Wang, B.-Z.; Gao, S. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, a linear phased array with pattern reconfigurable elements is studied to perform a scan angle extension of the array. The developed array can scan its main beam from -70o to 70o in its scanning plane. Compared with the traditional microstrip phased array, the scanning angle is extended remarkably.